Distributions, abundances and activities of microbes associated with the nitrogen cycle in riparian and stream sediments of a river tributary. (1st December 2016) - Kim, Haryun; Bae, Hee-Sung; Reddy, K. Ramesh; Ogram, Andrew
Abstract: River tributaries are ecologically important environments that function as sinks of inorganic nitrogen. To gain greater insight into the nitrogen cycle (N-cycle) in these environments, the distributions and activities of microbial populations involved in the N-cycle were studied in riparian and stream sediments of the Santa Fe River (SFR) tributaries located in northern Florida, USA. Riparian sediments were characterized by much higher organic matter content, and extracellular enzyme activities, including cellobiohydrolase, β-d -glucosidase, and phenol oxidase than stream sediments. Compared with stream sediments, riparian sediments exhibited significantly higher activities of nitrification, denitrification, dissimilatory nitrate reduction to ammonia (DNRA) and anaerobic ammonia oxidation; correspondingly, with higher copies of amoA (a biomarker for enumerating nitrifiers), nirS and nirK (for denitrifiers), and nrfA (for DNRA bacteria). Among N-cycle processes, denitrification showed the highest activities and the highest concentrations of the corresponding gene ( nirK and nirS ) copy numbers. In riparian sediments, substantial nitrification activities (6.3 mg-N kg soil −1 d −1 average) and numbers of amoA copies (7.3 × 10 7  copies g soil −1 average) were observed, and nitrification rates correlate with denitrification rates. The guild structures of denitrifiers and nitrifiers in riparian sediments differed significantly from those found in stream sediments, as revealed by analysis of nirS and archaeal amoA sequences. This study shows that riparian sediments serve as sinks for inorganic nitrogen loads from non-point sources of agricultural runoff, with nitrification and denitrification associated with elevated levels of carbon and nitrogen contents and extracellular enzyme activities. Graphical abstract: Highlights: Riparian of river tributary highly elevated the level of C and N, and soil enzymes. The elevated geochemistry enhanced the size and activity of N-cycling populations. Denitrification was tightly coupled with nitrification in N-cycle of tributaries. Denitrification was the central process in removing inorganic Ns from tributaries. Biogeochemistry impacted on shaping the structure of N-cycling genes.